Impact of commercial cellulase enzymes on the quality of clinacanthus nutans extract - Nabilah Binti Husain (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Clinacanthus nutans or Belalai Gajah had been use in traditional medicine to cure several types of disease such as snake bites and skin rashes. The production of aqueous extract from C. nutans is rare on market because it is quite challenging to produce extract from green leaves as it is content low yield of extract. Therefore, this project was carried to observe the impact of commercial cellulase enzyme on the yield recovery, total chlorophyll content and antioxidant activity of C. nutans extract. Total chlorophyll content (TCC) were analysed by using spectrophotometer while 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity are used to measure antioxidant capacity. The result shows that increase in concetration of enzyme will increase yield recovery, antioxidant activity and total chlorophyll content of C. nutans extract. Enzymatic treatment using cellulase enzyme shows that C. nutans leaves has higher volume yield compare to C. nutans stems which is 7.2 mL. The highest total chlorophyll content for C. nutans leaves and C. nutans stem are 49.50 and 39.06 respectively. For antioxidant activity, the highest value for C. nutans leaves is 70 % while for C. nutans stems is 21.28 %. Proximate analysis has been done to the best extract based on high yield of extract, total chlorophyll content and antioxidant activity. Therefore, the uses of cellulase enzyme not only increase the yield of C. nutans extract but also increase in the amount of total chlorophyll content and antioxidant activity.